Leadership performance in primary schools in Malaysia - Aziz @ Omar, Zanariah; Jusoff, Kamaruzaman; Tajul Urus, Sharina; Salleh, Salina; Abdul Rasit, Zarinah (Sacha and Diamond Academic Publishers, 2011)
Key Performance Indicators (KPI) is a tool used to measure performance. In Malaysia, the mission of the Ministry of Education is to develop a world-class quality education system which will realize the full potential of individuals and fulfill the aspiration of the Malaysian nation. In line with the aspiration, all Malaysian schools have to do their self-evaluation using Malaysian Education Quality Standards (SKPM) as the benchmarking instrument. No KPI has been developed and the purpose of the study is to develop a Key Performance Indicators (KPI) for schools in Malaysia which will help the Ministry in assessing and monitoring the schools’ performance, focusing on leadership performance. Surveys and interviews were done on 70 urban government’s Grade A primary schools in Selangor, Malaysia using stratified random sampling. The result showed that the overall average score in leadership performance for the schools range from 86.57% to 56.03%. Eleven schools score more than 80%. Leadership was measured using four dimensions specifically, ‘vision and values’, ‘communication and organizational performance’, ‘governance and social responsibilities’ and ‘ethical behaviour’. Average score for Governance and social responsibility is the highest compared to other sub-dimensions. This index is a generic innovative tool and the first of its kind in Malaysia. It is about providing transparency of the education system both within the school and in the Ministry as a whole. It can be further develop to address various criteria and needs of Malaysian education system and the region. It is not a long time for it to become the core of emerging method of managing education.